Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1525-1497.2006.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical student abuse during clinical clerkships in Japan

Abstract: OBJECTIVE: To assess the prevalence of medical student abuse during clinical clerkships in Japan. DESIGN: A cross‐sectional questionnaire survey. SETTING: Six medical schools in Japan. PARTICIPANTS: Final year (sixth‐year) and fifth‐year medical students in the period from September 2003 to January 2004. From a total of 559 students solicited, 304 (54.4%) returned the questionnaire, and 276 (49.4%: 178 male and 98 female) completed it. MEASUREMENTS: Prevalence of medical student abuse in 5 categories: ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
2
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 19 publications
9
64
2
13
Order By: Relevance
“…Our result supports the findings of previous studies on sexual harassment in the physician workplace: female physicians experience gender based harassment from colleagues, superiors, and patients (Komaromy et al 1993;Phillips and Schneider 1993;Witte et al 2006;Shrier et al 2007). Previous studies on the prevalence of sexual harassment among Japanese medical students and residents showed that 54.1% of female students and 58.3% of female residents experienced sexual harassment during their education or clinical training (Nagata- Kobayashi et al 2006Kobayashi et al , 2009. Our study, together with these findings, suggests that women experience gender-based mistreatment throughout their career.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our result supports the findings of previous studies on sexual harassment in the physician workplace: female physicians experience gender based harassment from colleagues, superiors, and patients (Komaromy et al 1993;Phillips and Schneider 1993;Witte et al 2006;Shrier et al 2007). Previous studies on the prevalence of sexual harassment among Japanese medical students and residents showed that 54.1% of female students and 58.3% of female residents experienced sexual harassment during their education or clinical training (Nagata- Kobayashi et al 2006Kobayashi et al , 2009. Our study, together with these findings, suggests that women experience gender-based mistreatment throughout their career.…”
Section: Discussionsupporting
confidence: 82%
“…Although a few studies have evaluated experience of disparate treatment based on gender among medical students and residents (Nagata-Kobayashi et al 2006, little is known about the prevalence of gender discrimination among Japanese physicians. In this study, we examined the perception of gender-based obstacles for women and the prevalence of experiences of gender discrimination among physicians in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, medical students who are subject to abusive behaviors are more likely to experience mental health issues such as post-traumatic stress [3,4], depression and low career satisfaction [5], and even suicidality [6]. More than three decades of studies have shown that the behavior of faculty, residents, and nurses toward medical students can be unprofessional and abusive, particularly during clinical clerkship rotations [1,5,7,8]. A meta-analysis demonstrated a high prevalence of harassment and discrimination toward medical trainees worldwide, with 59% of medical trainees experiencing at least one form of harassment or discrimination during their training [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mas e o estudante de Medicina? No início da década de 1980, foi difundido o termo "abuso" para descrever situações de violência vivenciadas por estudantes de Medicina na escola médica, à semelhança de violência de familiares contra crianças, tanto pela identificação de [19][20][21][22][23][24][25][26][27][28][29] . Entre as repercussões adversas sobre a saúde do estudante, os estudos citam depressão e alcoolismo, e sobre a relação do estudante com a própria profissão algumas consequências assinaladas foram maior cinismo, perda da capacidade de percepção do que é correto e desejo de abandonar a carreira médica 19,22,24,[27][28][29] .…”
Section: Violência Contra O Estudante De Medicinaunclassified